TO DETERMINE EFFICACY OF GRANISETRON VERSUS PLACEBO FOR REDUCING SHIVERING IN PATIENTS UNDERGOING LOWER SEGMENT CAESAREAN SECTION UNDER SPINAL ANAESTHESIA - Sana Abbas (Army Medical College Rawalpindi, 2021)
Objective: To determine the efficacy of granisetron versus placebo (saline) for reducing shivering in patients undergoing lower segment caeserian section under spinal anaesthesia.